Reconsidering the Resilience of Pastoralism from the Perspective of Reliability: The Case of Conflicts between the Samburu and the Pokot of Kenya, 2004-2009. (1st October 2021) - Konaka, Shinya
Abstract : This article explores an overlooked aspect of the 'resilience of pastoralism' in crises through an ethnographic case study of a series of conflicts between the Samburu and the Pokot in Kenya that erupted in 2004. Emery Roe's concepts of reliability professionals and real-time management of pastoralists are utilised as theoretical frameworks for this study. It was observed that the 'logic of high input variance matched by high process variance to ensure low and stable output variance' occurred through the formation of clustered settlements and an inter-ethnic mobile phone network. This case illustrates how pastoralists endured the conflict as reliability professionals.